Some novelties of Prunus subgenus Cerasus (Rosaceae) from Iran - Habibi, Meisam; Aritar, Farideh; Falahati Anbaran, Mohsen; Maleki Gisavandi, Hadi (Phytotaxa, 2022)
Prunus mazandaranica is described as a new species from north Iran. The new species has been placed in the sect. Microcerasus and could readily be distinguished from the closest relative, P. microcarpa subsp microcarpa, Prunus yazdiana, and Prunus paradoxa by indistinct brachyblasts, fasciculate inflorescence of 2–5 sessile or subsessile flowers with 10–12 unequal-sized stamens and glabrous style and ovary. Also, Prunus jacquemontii is recorded for the first time from northeast Iran. It is similar to P. griffithii morphologically, an endemic species distributed in Afghanistan, but distinguished from it by its glabrous leaves and glabrous style and ovary. Micromorphological features of pollen grains and leaf epidermal cells, surface are presented using Scanning Electron Microscopy. The diagnostic traits, a geographic distribution map, and detailed photos of the taxa are also presented here.